English Teachers’ Perception on the Implementation of Independent Learning Curriculum in Elementary Schools of Lima Kaum, Indonesia - Putra, Hendra Eka; Syarif, Hermawati; Zainil, Yetti (al-fikrah: Jurnal Manajemen Pendidikan, 2024)
The research problem was that the English teachers’ perceptions on the implementation of independent learning curriculum in elementary schools of Lima Kaum Indonesia had not been revealed. The aim of this research was to describe their perceptions on the implementation of this curriculum at those schools. This research was qualitative, a descriptive design. The informants were 5 English teachers who had implemented the independent learning curriculum from 4 elementary schools and were selected by using purposive sampling technique. The interview results were analyzed using the theory of (Miles and Huberman, 2014 in Safitri, 2022), namely: data reduction, data display, conclusion drawing and data verification. The results of the analysis showed that their perceptions on the implementation of the independent curriculum were various. In positive perception, they thought that the independent curriculum provides opportunities for them to vary learning methods and provides them opportunities to be more creative. In negative perception, they thought that there was no teacher forum available to discuss how to implement the independent curriculum that contribute to difficulty to incorporate it into the teaching and learning process. Therefore, they thought it was difficult for them to implement this curriculum due to a lack of direction from policy makers